Molecular Typing of Neisseria gonorrhoeae Isolates by Opa-Typing and Ribotyping in New Delhi, India - Pejvak Khaki; Preena Bhalla; Ahmad Mir Fayaz; Sohiela Moradi Bidhendi; Majid Esmailzadeh; Pawan Sharma (International Journal of Microbiology)
Control and preventive measures for gonococcal infections are based on precise epidemiological characteristics of N. gonorrhoeae isolates. In the present study the potential utility of opa-typing and ribotyping for molecular epidemiological study of consecutive gonococcal strains was determined. Sixty gonococcal isolates were subjected to ribotyping with two restriction enzymes, AvaII and HincII, and opa-typing with TaqI and HpaII for epidemiological characterization of gonococcal population. Ribotyping with AvaII yielded 6 ribotype patterns while twelve RFLP patterns were observed with HincII. Opa-typing of the 60 isolates revealed a total 54 opa-types, which 48 were unique and 6 formed clusters. Fifty-two opa-types were observed with TaqI-digested PCR product while opa-typing with HpaII demonstrated 54 opa-types. The opa-types from isolates that were epidemiologically unrelated were distinct, whereas those from the sexual contacts were identical. The results showed that opa-typing is highly useful for characterizing gonococcal strains from sexual contacts and has more discriminatory than ribotyping that could differentiate between gonococci of the same ribotype. The technique even with a single restriction enzyme has a high level of discrimination (99.9%) between epidemiologically unrelated isolates. In conclusion, the molecular methods such as opa-typing and ribotyping can be used for epidemiological characterization of gonococcal strains.